Association between DASH diet and metabolic syndrome in US adults: a cross-sectional study - Liu, Jianing; Yang, Rui; Ma, Pei; Zhu, Xiaobo (Frontiers in Public Health, 2025)
ObjectiveMetabolic syndrome (MetS) is a global issue increasingly threatening human health and the quality of life. This study aimed to explore the relationship between the Dietary Approaches to Stop Hypertension (DASH) diet and MetS, with the goal of providing insights into how dietary interventions may be associated with MetS.MethodsWe utilized data from the National Health and Nutrition Examination Survey 2005–2008 and divided DASH scores into five quintile groups. We included individuals over the age of 18 who underwent two 24-h dietary recalls administered by trained interviewers to calculate the DASH score. The chi-square test or Kruskal–Wallis test was used to compare the variable differences between the groups. A logistic regression model was used to analyze the association between DASH and MetS. The subgroup analysis was performed to explore the association between DASH diet and MetS in different populations. And we further explored the relationship between DASH and 5 particular MetS items in depth.ResultsThe final sample size was 8,780 individuals, with DASH scores ranging from 18 to 37. The proportion of women, younger individuals, non-Hispanic Blacks, low-income individuals, smokers, and those with MetS gradually decreased from Q1 to Q5 quintile groups. After adjusting for all variables, the odds ratio of MetS risk in the highest DASH quintile (Q5) compared with the lowest (Q1) was 0.60 (0.48, 0.77). The subgroup analyses revealed that the inverse association between DASH score and MetS risk was more pronounced among women, Whites, high-income individuals, those with a college degree or higher, those who were physically active, and never smokers. Subsequently, we discovered that DASH levels are significantly negatively correlated with waist circumference (WC), fasting plasma glucose (FPG), triglycerides (TG), and systolic blood pressure (SBP), while exhibiting a positive correlation with high-density lipoprotein cholesterol (HDL-C) through RCS curves and linear regression.ConclusionOur findings imply that higher adherence to the DASH diet is inversely associated with the risk of MetS, with pronounced effects on WC, FPG, SBP, DBP, TG, and HDL.